2005
DOI: 10.1021/cg050352n
|View full text |Cite
|
Sign up to set email alerts
|

Tapes, Sheets, and Prisms. Identification of the Weak C−F Interactions that Steer Fullerene−Porphyrin Cocrystallization

Abstract: Tetra(pentafluorophenyl)porphyrin (H 2 TPFPP) has been cocrystallized with C 60 from arene solvents to give H 2 TPFPP‚ C 60 , 1, H 2 TPFPP‚C 60 ‚8Benzene, 3, and 3H 2 TPFPP‚2C 60 ‚6Toluene, 4. Their X-ray structures have been determined to identify the supramolecular interactions that lead to tape, sheet, and prismatic packing motifs. In addition to close fullerene-porphyrin π-π interactions, attractive C-F‚‚‚H-C interactions are important in connecting the C 6 F 5 groups of one porphyrin to the pyrrole positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 23 publications
0
33
0
Order By: Relevance
“…An informative example is provided by the cocrystallate H 2 TPFP‚C 60 (H 2 TPFP ) tetra(pentafluorophenyl)porphyrin), which, as shown in Figure 4, combines the strict tetragonal register of alternating fullerenes and porphyrins with 2D sheets connected by (pentafluorophenyl)porphyrin C-F‚‚‚H-C hydrogen bridge interactions. 17 Although this structure postdated the fullerenepillared sheet structures discussed below, it illustrates the developing concept of engineering extended framework solids using the fullerene-porphyrin molecular attraction as a primary organizational element.…”
Section: Fullerene-porphyrin and Fullerene-metalloporphyrin Cocrystalmentioning
confidence: 96%
“…An informative example is provided by the cocrystallate H 2 TPFP‚C 60 (H 2 TPFP ) tetra(pentafluorophenyl)porphyrin), which, as shown in Figure 4, combines the strict tetragonal register of alternating fullerenes and porphyrins with 2D sheets connected by (pentafluorophenyl)porphyrin C-F‚‚‚H-C hydrogen bridge interactions. 17 Although this structure postdated the fullerenepillared sheet structures discussed below, it illustrates the developing concept of engineering extended framework solids using the fullerene-porphyrin molecular attraction as a primary organizational element.…”
Section: Fullerene-porphyrin and Fullerene-metalloporphyrin Cocrystalmentioning
confidence: 96%
“…This shorter separation has been attributed to an additional interaction between the electron density of a 6:6 ring juncture of the fullerene and the electropositive center of the porphyrin. Moreover, DFT calculations have shown that in the case of TPP the ortho -C-H··· π interactions increases π-π interactions for as much as 20% the when four C-H bonds are involved 266. Fullerenes are known to encapsulate various species, and the co-crystallization of a metal oxide cluster inside an icosahedral C 80 fullerene with Ni OEP was recently reported by Balch et al306…”
Section: Porphyrins and Fullerenes Architecturementioning
confidence: 97%
“…These cocrystals have been shown to form ordinate arrays of various shapes, ranging from tapes to sheets and other 3-D architectures that are largely dictated by the size of the C 60 and the substituents on the porphyrin. Pre-assembled porphyrins arrays can be used as well 266,267,279,284,305. The photonic properties of these materials depend on the electronic interactions between the two components, which arises from the solid state architecture.…”
Section: Porphyrins and Fullerenes Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…Samples stored in air and ambient light are stable for more than one month with no observed decomposition of the chromophores indicated by UV-visible spectroscopy. Considering the previous crystallographic data, 9 one possible molecular arrangement is with C 60 sandwiched between porphyrin molecules. Using the crystal data (fullerene diameter of 0.75 nm, and a porphyrin–C 60 distance of 0.26 nm) a 7 nm thick film would have ca.…”
mentioning
confidence: 98%